FAKTOR-FAKTOR YANG MEMPENGARUHI KEBERHASILAN SISWA KELAS 2 TMO SMK TEXMACO SEMARANG PADA MATA DIKLAT SERVICE ENGINE DAN KOMPONEN-KOMPONENNYA - Soleh, Ahmad; Pramono, -; Suratno, - (Jurnal Pendidikan Teknik Mesin, 2009)
This research aimed to determine what factors are significantly influencingstudent success Grade 2 Semarang TMO on Texmaco Vocational Training ServiceEngine Eye and Its Components Year 2008/2009 lesson. Population in this research areall 2nd grade students SMK Texmco Semarang TMO totaling 67 students. Variables inthis study are the factors that affect student success in training the eye and the serviceengine components. Data collection method used is the questionnaire method, while forthe data analysis technique using factor analysis. Conclusions obtained from this studyare the factors that influence the success of 2nd grade students at TMO TexmacoVocational Training Service Engine Eye and Its Components of internal factors andexternal factors. Advice can be given from the results of the research is to achieveoptimal student success if supported by the positive synergies between the student(internal factors) as the subject of study with the school component, parents, and socialenvironment (external factors).Key words: Succes factor, engine service, vocational training